The Medieval Luther - Helmer, Christine (Mohr Siebeck, 2020)
Staging a conversation among distinguished Luther scholars, historians of Christianity, and philosophers, The Medieval Luther makes the case that it is impossible to understand Luther's most important doctrines without exploring his philosophical inheritance. After all, Luther was an ardent participant in and contributor to the philosophical disputes of the late Middle Ages. By situating Luther's theology in relation to medieval healing practices, mysticism, biblical interpretation, and politics, this volume blurs the historiographical line between the medieval and early modern periods. Offering an expansive appreciation of the Middle Ages for his thought, The Medieval Luther is indispensable for any future study of the Reformation's leading figure.